2016
DOI: 10.1038/srep37492
|View full text |Cite
|
Sign up to set email alerts
|

The coordinated roles of miR-26a and miR-30c in regulating TGFβ1-induced epithelial-to-mesenchymal transition in diabetic nephropathy

Abstract: MicroRNAs (miRNAs) play vital roles in the development of diabetic nephropathy. Here, we compared the protective efficacies of miR-26a and miR-30c in renal tubular epithelial cells (NRK-52E) and determined whether they demonstrated additive effects in the attenuation of renal fibrosis. TGFβ1 suppressed miR-26a and miR-30c expression but up-regulated pro-fibrotic markers in NRK-52E cells, and these changes were also found in the kidney cortex of 40-week-old diabetic Otsuka Long-Evans Tokushima fatty (OLETF) rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 48 publications
1
48
0
Order By: Relevance
“…In our previous research, we demonstrated that ERK1/2 plays an important role in regulating renal tubular epithelial cell EMT processes (Zheng et al, ). In this study, we found that the miR‐4756 mimic significantly increased ERK1/2 phosphorylation in the presence of HSA.…”
Section: Resultsmentioning
confidence: 91%
“…In our previous research, we demonstrated that ERK1/2 plays an important role in regulating renal tubular epithelial cell EMT processes (Zheng et al, ). In this study, we found that the miR‐4756 mimic significantly increased ERK1/2 phosphorylation in the presence of HSA.…”
Section: Resultsmentioning
confidence: 91%
“…MicroRNAs (miRNAs) are short noncoding RNAs that modulate fundamental cellular processes, and existed researches showed several miRNAs are highly associated with the EMT, such as miR‐30c, miR‐23a/b, miR‐130b, and miR‐302 family (Bai, Geng, Zhou, Tian, & Li, ; Lipchina, Elkabetz, & Hafner, ; Liu et al, ; Zhao, Yin, & Li, ; Zheng, Guan, & Jia, ). Among them, miR‐302 family, including miR‐302a, miR‐302b, miR‐302c, and miR‐302d, are located on human chromosome 4q25.…”
Section: Discussionmentioning
confidence: 99%
“…Real‐time quantitative polymerase chain reaction (qPCR) was performed in a Roche Lightcycler 480II (Roche, Basle, Switzerland) using a SYBR Green qPCR Kit (Takara). Relative gene expression was calculated using the 2 −ΔΔCt method and 18 s as an internal control . The primers used are listed in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Relative gene expression was calculated using the 2 −ΔΔCt method and 18 s as an internal control. 16 The primers used are listed in Table 1.…”
Section: Extraction Of Ribonucleic Acid (Rna) and Quantitative Realmentioning
confidence: 99%